Analisis Kesalahan Siswa dalam Menyelesaikan Soal Matematika Di SMP Negeri 1 Serui - Mulyadi Mulyadi; Annisa Fatmayanti (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
This study aims to describe the location, types, and causes of student errors in solving math problems in SPLDV material. The subjects were 3 students of class IX in the odd semester of the 2022/2023 academic year at SMP Negeri 1 Serui. The research instrument is in the form of SPLDV questions with a total of 2 items. The results showed that the mistakes made by many students were not writing down important information on the questions, making mistakes in making mathematical models, making mistakes in calculating operations, and not writing the final conclusions. While the types of errors made are conceptual, procedural, and also technical errors. Furthermore, it is known that the factors that cause errors are a lack of understanding of the SPLDV concept, errors in arithmetic operations, and lack of accuracy.